The internal conversation of the Old Testament - McEntire, Mark Harold (Smyth & Helwys bible commentary, 2018)
The Old Testament as a blending of traditions -- How do we understand our origins? -- How do we remember our ancestors? -- How do we portray our heroes? -- How do we govern ourselves? -- How do we measure our successes and failures? -- How do we think about the places where we live? -- Reflections of a composite text